Let’s MOVE: Empowering Emerging Adulthood Lives with Acceptance and Commitment Therapy Training for Greater Well-Being and Self-Compassion - Juaninda, Carrenina Prilly; Oriza, Imelda Ika Dian (Bulletin of Counseling and Psychotherapy, 2024)
Emerging adulthood is a transitional phase characterized by instability and uncertainty, which can lead to psychological distress among individuals transitioning from high school to adulthood. This study utilized an experimental design to assess the effectiveness of Acceptance and Commitment Therapy (ACT) training in improving subjective well-being and self-compassion. We recruited 18 emerging adults, specifically those who had recently graduated from high school, with 8 individuals in the experimental group and 10 in the control group. The training comprised four sessions, each lasting two hours. The Satisfaction with Life Scale (SWLS) and the Self-Compassion Scale (SCS) were used for measurement. Data analysis using independent sample t-tests indicated significant improvements in subjective well-being and self-compassion in the experimental group compared to the control group. The effects of the intervention remained strong at the 3-week follow-up. These findings suggest that ACT training is effective in enhancing subjective well-being and self-compassion among emerging adults experiencing psychological distress.